Virtual inertia calculation and virtual power system stabiliser design for stability enhancement of virtual synchronous generator system under transient condition - Ony Asrarul Qudsi; Adi Soeprijanto; Ardyono Priyadi (IET Energy Systems Integration)
Abstract Enhancing the stability of the Virtual Synchronous Generator (VSG) under transient conditions has become a new challenge for VSG operation. This paper presents the design of a Virtual Power System Stabiliser (VPSS) with virtual inertia calculations for the stability enhancement of the VSG system under transient conditions. The virtual inertia is calculated by considering the transient conditions resulting from a three‐phase ground fault and the allowable phase margin in the VSG. This aims to prevent the coupling effect, which can cause the active power loop control and reactive power loop control to operate non‐independently. Subsequently, the VPSS is specifically designed based on the determined virtual inertia characteristics. The VPSS design is developed by taking into account the phase angle shift of the VSG. The proposed combination of virtual inertia and VPSS is capable of providing accurate compensation for phase angle changes under transient conditions. To evaluate the performance of the proposed virtual inertia and VPSS, a system‐level VSG model is used to thoroughly analyse the system's performance. Based on the results and analysis, it is shown that the control strategy utilising the combination of virtual inertia and the proposed VPSS design can improve VSG stability under transient conditions.